Rate variation in parasitic plants: correlated and uncorrelated patterns among plastid genes of different function - Young, Nelson D (BioMed Central, 2005)
BACKGROUND: The analysis of synonymous and nonsynonymous rates of DNA change can help in the choice among competing explanations for rate variation, such as differences in constraint, mutation rate, or the strength of genetic drift. Nonphotosynthetic plants of the Orobanchaceae have increased rates of DNA change. In this study 38 taxa of Orobanchaceae and relatives were used and 3 plastid genes were sequenced for each taxon. RESULTS: Phylogenetic reconstructions of relative rates of sequence evolution for three plastid genes (rbcL, matK and rps2) show significant rate heterogeneity among lineages and among genes. Many of the non-photosynthetic plants have increases in both synonymous and nonsynonymous rates, indicating that both (1) selection is relaxed, and (2) there has been a change in the rate at which mutations are entering the population in these species. However, rate increases are not always immediate upon loss of photosynthesis. Overall there is a poor correlation of synonymous and nonsynonymous rates. There is, however, a strong correlation of synonymous rates across the 3 genes studied and the lineage-speccific pattern for each gene is strikingly similar. This indicates that the causes of synonymous rate variation are affecting the whole plastid genome in a similar way. There is a weaker correlation across genes for nonsynonymous rates. Here the picture is more complex, as could be expected if there are many causes of variation, differing from taxon to taxon and gene to gene. CONCLUSIONS: The distinctive pattern of rate increases in Orobanchaceae has at least two causes. It is clear that there is a relaxation of constraint in many (though not all) non-photosynthetic lineages. However, there is also some force affecting synonymous sites as well. At this point, it is not possible to tell whether it is generation time, speciation rate, mutation rate, DNA repair efficiency or some combination of these factors.